2022
DOI: 10.3390/bioengineering9100494
|View full text |Cite
|
Sign up to set email alerts
|

Review of Bioactivity, Isolation, and Identification of Active Compounds from Antrodia cinnamomea

Abstract: Antrodia cinnamomea is a precious and popular edible and medicinal mushroom. It has attracted increasing attention due to its various and excellent bioactivities, such as hepatoprotection, hypoglycemic, antioxidant, antitumor, anticancer, anti-inflammatory, immunomodulation, and gut microbiota regulation properties. To elucidate its bioactivities and develop novel functional foods or medicines, numerous studies have focused on the isolation and identification of the bioactive compounds of A. cinnamomea. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…To date, more than 200 compounds, including polysaccharides, triterpenoids, ubiquinone derivatives, maleic and succinic acid derivatives, benzene derivatives, and glycoprotein, have been isolated from the AC fruiting bodies and mycelia [ 2 , 3 , 25 ]. Among them, ergostane and lanostane triterpenoids are considered the main bioactive compounds of AC, of which ergostane-type triterpenoids are considered to be the unique bioactive compounds of AC and are only found in its fruiting bodies [ 1 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, more than 200 compounds, including polysaccharides, triterpenoids, ubiquinone derivatives, maleic and succinic acid derivatives, benzene derivatives, and glycoprotein, have been isolated from the AC fruiting bodies and mycelia [ 2 , 3 , 25 ]. Among them, ergostane and lanostane triterpenoids are considered the main bioactive compounds of AC, of which ergostane-type triterpenoids are considered to be the unique bioactive compounds of AC and are only found in its fruiting bodies [ 1 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A. cinnamomea presents various biological activities, such as hepatoprotective, antitumor, antioxidant, antiviral, antivasodilation, hypoglycemic, immunoregulatory, and gut microbiota regulatory [ 2 , 3 , 4 , 5 ]. The main bioactive compounds of A. cinnamomea include triterpenoids (such as antcins A, antcins B, antcins C, antcins H, antcins K, methylantcinate, and sulphurenic acid), polysaccharides, ubiquinone derivatives (such as antroquinonol, antroquinonol B, antroquinonol C, antroquinonol D, antroquinonol L, antroquinonol M, and 4-acetyantroquinonol B), maleic and succinic acid derivatives (such as antrodins A, antrodins B, antrodins C, antrodins D, and antrodins E), and benzene derivatives [ 4 , 6 , 7 , 8 ]. What is more, some compounds, such as antcins C, antcins K, antrodins B, antrodins C, and 4-acetyantroquinonol B, with excellent bioactivities from A. cinnamomea , have not been found in other edible and medicinal fungi so far [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antrodia cinnamomea (AC), also known as Taiwanofungus camphoratus, is a species of fungus used as a medicinal mushroom that is endemic to Taiwan. So far, multiple compounds, such as polysaccharide, polyphenol, and triterpenoid, have been identified from AC [2,3]. Prior work revealed that the pharmacological actions of AC cover antioxidant, hepatoprotective, antihyperlipidemic, anti-inflammatory, anticancer, and immunomodulatory activities [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…So far, multiple compounds, such as polysaccharide, polyphenol, and triterpenoid, have been identified from AC [2,3]. Prior work revealed that the pharmacological actions of AC cover antioxidant, hepatoprotective, antihyperlipidemic, anti-inflammatory, anticancer, and immunomodulatory activities [2,3]. Chronic kidney disease (CKD) is a progressive disease that can originate in the earliest stage of life [4].…”
Section: Introductionmentioning
confidence: 99%